The effect of event impact on fear of missing out: the chain mediation effect of coping styles and anxiety - He, Bofeng; Tan, Zhenjing; Lai, Kaiying; Qiu, Boyu; Wang, Suiping (Frontiers in Psychology, 2024)
The fear of missing out is a generalized anxiety stemming from the possibility of not being present at new events or advantageous situations of others. To explore potential mechanisms, a survey measuring the impact of an event, coping style, anxiety, and fear of missing out was conducted with 1014 college students(367 males and 647 females,aged 19-24years). In addition, the study delved deeper into the dimensions of intrusion, avoidance, and hyperarousal concerning the impact of an event, examining their roles in coping style, anxiety, and fear of missing out.Results showed that: (1) The impact of an event could predict the fear of missing out positively.(2) A more positive coping style is negatively associated with anxiety. (3)A chain mediation effect of coping style and anxiety is observed in the path from hyperarousal and avoidance to the fear of missing out. (4) In contrast to the hyperarousal or avoidance, the path from intrusion to the fear of missing out is mediated by anxiety but not coping style. A chain mediation effect of coping style and anxiety is observed in the path from high arousal and avoidance impact of an event to the fear of missing out. (4) In contrast, the high arousal or avoidance impact of an event, the path from intrusion impact of event to the fear of missing out is mediated by anxiety but not coping style. These findings motivate us to implement different intervention tactics for varying impacts of events.